The effect of neuropeptide FF in the amygdala kindling model. (27th October 2015) - Buffel, I.; Meurs, A.; Portelli, J.; Raedt, R.; De Herdt, V.; Poppe, L.; De Meulenaere, V.; Wadman, W.; Bihel, F.; Schmitt, M.; Vonck, K.; Bourguignon, J.‐J.; et al.
Abstract : Objective: Neuropeptide FF (NPFF) and its receptors (NPFF1 R and NPFF2 R) are differentially distributed throughout the central nervous system. NPFF reduces cortical excitability in rats when administered intracerebroventricularly (i.c.v.), and both NPFF and NPFF1 R antagonists attenuate pilocarpine‐induced limbic seizures. In this study, our aim was to determine whether NPFF exerts anticonvulsant or anti‐epileptogenic effects in the rat amygdala kindling model for temporal lobe seizures. Methods: Male Wistar rats were implanted with a recording/stimulation electrode in the right amygdala and a cannula in the left lateral ventricle. In a first group of animals, the afterdischarge threshold (ADT) was determined after a single i.c.v. infusion of saline ( n = 8) or NPFF (1 nmol/h for 2 h; n = 10). Subsequently, daily infusion of saline ( n = 8) or NPFF (1 nmol/h for 2 h; i.c.v.; n = 9) was performed, followed by a kindling stimulus (ADT+200 μA). Afterdischarge duration and seizure severity were evaluated after every kindling stimulus. A second group of rats ( n = 7) were fully kindled, and the effect of saline or a high dose of NPFF (10 nmol/h for 2 h, i.c.v.) on ADT and the generalized seizure threshold (GST) was subsequently determined. Results: In naive rats, NPFF significantly increased the ADT compared to control (435 ± 72 μA vs 131 ± 23 μA [ P < 0.05]). When rats underwent daily stimulations above the ADT, NPFF did not delay or prevent kindling acquisition. Furthermore, a high dose of NPFF did not alter ADT or GST in fully kindled rats. Conclusions: I.c.v. administration of NPFF reduced excitability in the amygdala in naive, but not in fully kindled rats, and had no effect on kindling acquisition.